Dinamika Peer Group pada Mahasiswa Fakultas Psikologi Unika Atma Jaya: Penelitian Cross-sectional dengan Metode Sosiometri - Ferdinand Prawiro; Debrita Purbaningrum (MANASA, 2021)
The current study aimed at describing the life of undergraduate student of Faculty of PsychologyAtma Jaya Catholic University of Indonesia through peer group dynamics. Peer group oftendetermined who will be asked to join for doing an academic group task (‘kelompok tugas’), whowill be chosen to hang out together (‘teman nongkrong’), dan who can be trusted to talk aboutpersonal issues (‘teman curhat’). Peer groups were not static, thus we also explored peer groupdynamics based on time dimension, i.e. beginning (‘semester 2’), middle (‘semester 4’) and end(‘semester 6’) period of study. An explorative-descriptive research design with sociometric methodswere used in the study. Participants were 126 undergraduate students from the same year of entry.Data were analyzed by means of sociomatrix, choice status of a person and sociogram. The resultsshowed the differences peer group dynamics between situations (kelompok tugas, teman nongkrong,teman curhat) and between periods of study (semester 2, semester 4, semester 6). This studyrevealed the possible use of sociometric methods for policy socialization strategy and as a methodfor identifying potential academic and non-academic problems.